The Antifungal Activity of HMA, an Amiloride Analog and Inhibitor of Na+/H+ Exchangers - Vu, Kiem; Blumwald, Eduardo; Gelli, Angie (Frontiers in Microbiology, 2021)
Abstract One path toward identifying effective and easily accessible antifungals is to repurpose commonly used drugs. Amiloride, a widely used diuretic, inhibits different isoforms of Na+/H+ exchangers, Na+ channels and Na+/Ca2+ exchangers. Here, we found that amiloride had poor antifungal activity against isolates of Cryptococcus prompting the examination of the amiloride analogue, HMA [5-(N,N-hexamethylene)amiloride]. HMA possesses strong activity against Na+/H+ exchangers (NHEs) and little K+-associated toxicity since HMA has only minimal inhibitory effects toward epithelial sodium channels (ENaC), the diuretic and antikaliuretic target of amiloride. Although HMA produced a robust dose-dependent growth inhibition of several fungal isolates, susceptibility assays revealed modest MICs against isolates of Cryptococcus. A checkerboard dilution strategy resulted in fractional inhibitory concentrations (FIC) < 0.5, suggesting that HMA displays synergy with several antifungal azole drugs including posaconazole, voriconazole and ketoconazole. Itraconazole and ravuconazole showed moderate synergy with HMA across all tested fungal isolates. In combination with HMA, ravuconazole had MICs of 0.004 to 0.008 µg/ml, a ~16-fold reduction compared to MICs of ravuconazole when used alone and significantly more effective than the overall MIC90 (0.25 µg/ml) reported for ravuconazole against 541 clinical isolates of Cryptococcus neoformans. In combination with azole drugs, MICs of HMA ranged from 3.2 µM to 26 µM, HMA was not cytotoxic at concentrations ≤ 8 µg/ml, but MICs were above the reported HMA Ki of 0.013 – 2.4 µM for various Na+/H+ exchangers. Our results suggest that HMA has limited potential as a monotherapy and may have additional targets in fungal/yeast cells since strains lacking NHEs remained sensitive to HMA. We determined that the hydrophobic substituent at the 5-amino group of HMA is likely responsible for the observed antifungal activity and synergy with several azoles since derivatives with bulky polar substitutions showed no activity against Cryptococcus, indicating that other 5-substituted HMA derivatives could possess stronger antifungal activity. Moreover, substitution of other positions around the pyrazine core of HMA have not been investigated but could reveal new leads for antifungal drug development.